Measurement, processing and analysis of stress magnetocardiograms. Issue 1 (May 2021) - Kesavaraja, C; Sengottuvel, S; Patel, Rajesh; Khan, Pathan Fayaz; Swain, Pragyna Parimita; Gireesan, K
Abstract: Magnetocardiography (MCG) measures weak magnetic fields originating due to the electrical activity of the heart. MCG offers distinct diagnostic information on the cardiac electrophysiology in a variety of dysfunctions. This list includes myocardial ischemia, which is associated with reduced blood supply to the heart, electrically manifested as changes in the ST segment of the cardiac cycle. As opposed to the conventional measurement of electrocardiogram (ECG) on subjects undergoing physical stress test to investigate these ST changes, rest MCG itself has been demonstrated to be more sensitive. Considerable interest exists among researchers to investigate MCG signals measured during physical exertion as well to explore the possibilities of improvements in its sensitivity. This paper portrays the MCG measurements of a few subjects under rest and during moderate cycling in supine posture using a non-magnetic bicycle ergometer. The work details the signal processing steps followed in processing MCG to refine the signal quality in computing the parameter, ST fluctuation score in an automated manner. Significant changes are seen on the ST fluctuation scores measured on a few healthy subjects across rest and stress conditions. These results persuade its possible use on MCG measured on subjects with ischemic heart diseases by treating this analysis as baseline measurements.